Bentuk Penyajian Tari Rapa’I Geleng di Sanggar Pocut Baren MAN Model Banda Aceh - Yuli Astuti; Samsuri Samsuri; Ilham Septian (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This study aims to describe the presentation form of Rapa'i Geleng dance in Sanggar Pocut Baren MAN Model Banda Aceh. The method used is descriptive qualitative with data collection techniques through observation and interviews. The results showed that the presentation of Rapa'i Geleng dance consists of three stages and four acts, namely: seulaweut (opener), saleum (greeting), kisah (content), and lanie (closing). Each act has a distinctive structure of movement, Rapa'i beat, and poetry. In addition to functioning as entertainment, this performance is also a medium for proselytizing and preserving the cultural and religious values of the Acehnese people. The main property used is Rapa'i, Islamic nuanced closed clothing, and a movement system that reflects local wisdom.